2011
DOI: 10.1083/jcb.201101021
|View full text |Cite
|
Sign up to set email alerts
|

Interruption of intrachromosomal looping by CCCTC binding factor decoy proteins abrogates genomic imprinting of human insulin-like growth factor II

Abstract: CCCTC binding factor (CTCF) mutants that cannot bind components of the polycomb repressive complex-2 (PRC2) do not form the chromatin loops that regulate monoallelic gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 47 publications
1
77
0
Order By: Relevance
“…Total protein extracts of cultured cells in each group were prepared using nuclear and cytoplasmic extraction reagents (Pierce, Rockford, Ill., USA) as previously described [Zhang et al, 2011]. The protein concentration was measured using BCA Protein Assay Reagent (Pierce).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Total protein extracts of cultured cells in each group were prepared using nuclear and cytoplasmic extraction reagents (Pierce, Rockford, Ill., USA) as previously described [Zhang et al, 2011]. The protein concentration was measured using BCA Protein Assay Reagent (Pierce).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…This activity is attributable to the presence of binding sites within the DMD for the vertebrate insulator protein, CTCF. As inferred by chromatin conformation capture assays, the CTCF-bound maternal DMD causes the locus to adopt a three-dimensional conformation, which occludes the activation of Igf2 by the enhancers, leading to the activation of H19 expression (Engel et al 2006;Kurukuti et al 2006;Zhang et al 2011). Importantly, association of CTCF with its binding sites is inhibited by the presence of DNA methylation.…”
Section: X-chromosome Inactivation: a Model For The Establishment Of mentioning
confidence: 99%
“…57 Abolishing this ability of CTCF decreased H3K27 methylation, compromised DNA loop formation and reactivated the normally suppressed maternal IGF2 allele. 56 Whether direct interactions between cohesin and PRC2 exist to regulate loop formation and histone methylation remains unclear. Future studies should clarify relationships between cohesin, CTCF, lncRNA, PRC2 and other factors as well as identify the relative contribution of all of these molecules to chromatin looping and histone post-translational modifications across the genome.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…In addition, a recent study demonstrated the involvement of the polycomb repressive complex-2 (PRC2) in loop formation at IGF2-H19. 56 Once recruited to IGF2-H19 in a CTCF-dependent fashion, PRC2 methylates histone H3 lysine 27 (H3K27) within the promoter region of the maternal IGF2 allele to ensure its efficient silencing. 57 Abolishing this ability of CTCF decreased H3K27 methylation, compromised DNA loop formation and reactivated the normally suppressed maternal IGF2 allele.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%